BRAND PREFERENCE BETWEEN APPLE AND SAMSUNG SMARTPHONE IN MANADO - Goni, Windy (FEB Universitas Sam Ratulangi Manado, 2013)
Branding is increasingly being used as a strategy for managing markets plays a very vital role in consumer buying decision. It has already proven that brands are are the company’s most important asset. The objective of this study is to provide the information about the brand preference of smartphone in Manado and to reveal which brand that become brand preference in Manado. This research uses two important indicators that are brand equity and brand image. The method that is used in this research is qualitative method in which, the primary data is collected using interview. The respondents of the study are Manado citizen who own Apple and Samsung smartphone. This study show that brand with high value of brand equity and image will result in having high brand preference among Manado people. The findings reveal that Apple has stronger brand preference more than Samsung among people in Manado. Hence, the findings provide a solid foundation for purchase decisions of Apple smartphone among Manado people, which is Apple smartphone would increase the products sales within the Manado market for smartphones. Keywords: brand equity, brand image, brand preference, smartphone, qualitative